MOVEMENT TECHNIQUE ANALYSIS AND SPORTS INJURIES PREVENTION IN THE ELDERLY PHYSICAL TRAINING - Sun,Jingzhu (2023)
ABSTRACT Introduction: Physical training for the elderly is extremely popular. However, there is a lack of analysis on sports injuries in the elderly. Objective: Study the analysis of movement in sports training techniques and preventing sports injuries in the elderly. Methods: Participating in a 15-minute running and warm-up activity before using the standard FMS test kit, they followed seven test movements, each repeated three times; they did so during six weeks of training based on the recommendations for the prevention of sports injuries presented in this paper. Results: Among the 14 elderly subjects with a total FMS score <14 points, most functional motor scores were 15-16 points, of which 19 points were high, and 9 points were low. In the intervention based on the perspective of sports injuries, the FMS measurement value of the elderly was much better than before, and the evaluation of the technical analysis of movement after the correction was significantly higher than before. Conclusion: The prevention of sports injuries proposed in this paper can effectively help the elderly to prevent sports injuries. This paper considers the FMS trial design as an example for analyzing movements in sports training of the elderly and formulating standards. Level of evidence II; Therapeutic studies - investigation of treatment outcomes.